Thermal behavior of lithium-ion battery in microgrid application: Impact and management system - Hasani A.H.; Mansor M.; Kumaran V.; Zuhdi A.W.M.; Ying Y.J.; Hannan M.A.; Hamid F.A.; Rahman M.S.A.; Salim N.A. (John Wiley and Sons Ltd, 2023)
Cooling; Cooling systems; Energy storage; Heat pipes; Ions; Life cycle; Lithium-ion batteries; Microgrids; Phase change materials; Solid-State Batteries; Temperature control; Temperature measurement; Thermal management (electronics); Battery thermal managements; Energy storage systems; Internal temperature; Operating temperature; Solid-state cooling; Temperature uniformity; Thermal management systems; Thermally conductive fillers; Battery management systems